Implementasi Pemeriksaan Laboratorium Ibu Hamil Sebagai Upaya Deteksi Dini Komplikasi Kehamilan Dan Persiapan Persalinan Di Desa Batursari Wilayah Kerja Puskesmas Sirampog - Khoeroh, Himatul; Susilowati, Endang (Akademi Kebidanan Bunga Husada Samarinda, 2024)
ANC services are in accordance with the care service program policy Antenatal care must comply with the 10 T standard, which includes Hb examination, urine protein examination if indicated and urine glucose examination if indicated. The impact of abnormal laboratory results can affect the health status of pregnant women, especially complications during pregnancy and even childbirth. The aim of the research is to provide services in the form of implementing laboratory examinations for pregnant women through input, process and output elementsuse applied research methodswith a qualitative design presented descriptively. Results study showing element input Already Good from Source One Man (SDM), means infrastructure and funding Already integrated. On element process Laboratory examination services for pregnant women run well by showing results and explaining solutions for improvement, while the output elementThe results were found within a certain period of time from the initial visit to the next visit, from previously 18 pregnant women were at risk from 21 to 6 pregnant women who were at risk with details of 5 pregnant women of whom still experienced anemia and KEK (Calorie Energy Deficiency) and 1 other pregnant woman with the pre-eclampsia triad.